1999
DOI: 10.1111/j.1532-5415.1999.tb03848.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a Five‐Item Version of the Geriatric Depression Scale

Abstract: The 5-item GDS was as effective as the 15-item GDS for depression screening in this population, with a marked reduction in administration time. If validated elsewhere, it may prove to be a preferred screening test for depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
452
0
18

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 664 publications
(488 citation statements)
references
References 41 publications
4
452
0
18
Order By: Relevance
“…More than 22% of participants scored 2 or greater on the 5-item GDS, a cutpoint highly suggestive of clinical depression. 19 ERA-38 scale scores were normally distributed; Shapiro-Wilk test was 0.986 ( P ϭ .0004). For each of the 34 items describing age-associated decline, at least 25% of respondents stated that the item was definitely true or somewhat true, indicating that the described age-associated decline was an expected part of aging; for each of the four items describing maintaining health-related quality of life with aging, at least 21% of participants stated the item was definitely false or somewhat false, indicating that the described aspect of successful aging was not expected (complete data not shown, available by request).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…More than 22% of participants scored 2 or greater on the 5-item GDS, a cutpoint highly suggestive of clinical depression. 19 ERA-38 scale scores were normally distributed; Shapiro-Wilk test was 0.986 ( P ϭ .0004). For each of the 34 items describing age-associated decline, at least 25% of respondents stated that the item was definitely true or somewhat true, indicating that the described age-associated decline was an expected part of aging; for each of the four items describing maintaining health-related quality of life with aging, at least 21% of participants stated the item was definitely false or somewhat false, indicating that the described aspect of successful aging was not expected (complete data not shown, available by request).…”
Section: Resultsmentioning
confidence: 96%
“…These included (1) seven sociodemographic items; (2) the Medical Outcomes Study Short Form-12 (SF-12), a general health status measure containing physical component summary (PCS-12) and mental component summary (MCS-12) scales 15 (Both the PCS-12 and the MCS-12 have a mean of 50 and a standard deviation (SD) of 10 in the general U.S. population, with higher scores indicative of better physical and mental health. ); (3) 13 questions regarding ability to independently perform basic and instrumental activities of daily living (ADLs); 16,17 (4) the Charlson Comorbidity Scale modified for self-administration; 18 (5) the 5-item Geriatric Depression Scale (GDS); 19 and (6) two questions measuring intrinsic religiosity modified from a previously validated instrument. 20 Analysis ERA-38 scores were calculated and examined using simple descriptive statistics.…”
Section: Data Collectionmentioning
confidence: 99%
“…In their study of the psychometric properties of the GDS with younger populations, Rule, Harvey, and Dobbs (1989) found that the GDS is internally consistent (Cronbach's alpha = .82) and has established convergent validity with the Zung Self Rating Depression Scale (Zung, 1965) .97, and accuracy of .90 for predicting depression. In addition, significant agreement was found between depression diagnosis and the GDS-5 (Hoyl et al, 1999).…”
Section: Depressionmentioning
confidence: 77%
“…Time 4 (T4) was given to delayed treatment control participants only, serving as a 1-month follow-up assessment for this group. An abbreviated 5-item GDS (Hoyl et al, 1999) was administered weekly during the self-help treatment phase for both groups to monitor symptoms. Depressive symptoms were monitored during the 4-week delay phase for control group participants via two questions: 1) "Have you noticed any changes in your mood over the past week?"…”
Section: Designmentioning
confidence: 99%
“…Blood levels of the antioxidants, including alphaand gamma-tocopherols, retinol, beta-cryptoxanthin, alphaand beta-carotenes, lycopene, and lutein and zeaxanthin, were determined by high-performance liquid chromatography. Our structured questionnaire included socioeconomic and lifestyle-related factors, past/current history of illness, and some well-validated scales, such as the Geriatric Depression Scale (GDS) 5-item version [7] and the Hearing Handicap Inventory for the Elderly-Screening version (HHIE-S) [8].…”
Section: Outline Of the Kurabuchi Studymentioning
confidence: 99%